Bridging Local Identity and English Proficiency through CLIL: A Proposal for Implementation - Ainol Mardhiah; Muriya Ningrum; Diana Purwati (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study investigates the potential of Content and Language Integrated Learning (CLIL) as an approach for improving English language proficiency among high school students in Bener Meriah, Aceh, Indonesia. Leveraging the local identity and reputation of Bener Meriah as a leading coffee producer region, this study proposed a coffee-themed curriculum to be integrated in English learning with culturally relevant content. A systematic literature review (SLR) was conducted in accordance with PRISMA guidelines to explore the implementation of CLIL in high school EFL contexts. Using Google Scholar, an initial boolean search identified 87 articles published between 2020 and 2024. Through inclusion and exclusion criteria, 12 relevant studies were selected for final analysis. The findings reveal that (i) CLIL promotes language acquisition, contextual learning, and student motivation. However, (ii) challenges such as resource constraints, teacher training needs, and implementation costs must be addressed. Based on these findings, this article offers recommendations for CLIL integration and highlights its implications for education and economic development in EFL contexts, particularly Bener Meriah, where coffee farming is a primary source of livelihood.